Admissibility of Iqrar as Evidence: the Issue of Voluntariness from Syariah Principles Perspective - Azam Mohd Shariff, Ahmad; Rajamanickam, Ramalinggam; Kaur Harnam Singh, Parveen; Khadijah Md Lazim, Siti; Sofea Nurol Adzmi, Anna; Xin Xian, Lim; Faris Haikal Mad Zahudi, Muhammad; Noor Azira Tg. Zainudin, Tg. (International Journal of Engineering and Technology, 2018)
Iqrar is a form of bayyinah or evidence which could be tendered during trial at the syariah court. The syariah evidential principles renders it relevant and admissible with varying effect. Iqrar sorih or confession, once admitted by court, would become binding against the accused. In such a scenario, the court may convict the accused based on such confession without any need for further proof. On the other hand, the court may also admit an admission or iqrar kinayah but it could never convict the accused based on such admission alone. In other words, based on admissibility of such admission, a court could only convict the accused should such admission is further corroborated and strengthened by other evidence. This article however observes that the strength of a confession very mush depends on voluntariness of the maker of the confession. There is also some confusion among syariah practitioners as regards to the difference between both forms of iqrar. The conducted research is pure legal and qualitative in nature. Data and materials on iqrar confession and admission are collected via library research method. These data and materials are then analysed using critical and content methodologies.. This article analyses the relevancy and admissibility of iqrar confession and admission in the eyes of syariah evidential principles. It then strives at identifying problems relating to its admissibility and interpretation. This article eventually offers some ideas on ways of avoiding future misinterpretation of iqrar while simultaneously looking into some ideas on how to improve its application.Â
Keywords: Iqrar; Confession; Admission; Syariah Evidential Principles; Relevancy; Admissibility.